Da ideologia à autenticidade na compreensão dos pressupostos do acontecer do direito material no processo: uma aposta paradoxal na ação de direito como categoria hermenêutica - Hidalgo, Daniela Boito Maurmann (Universidade do Vale do Rio dos Sinos, 2008)
The present study deals with problems concerning the relation between substantive law and process, aiming at showing the denial, by the majority doctrine, of the action of the substantive law, considered mere slogan, is a great source of subtraction of the practical world, and therefore the infectivity of the process and the consequent non- concretization of the rights (pretensions) of substantive law, which depend on the process to be achieved. We aim at, in the (de)construction of the pre-comprehension of this relation, delineating how this relation has developed to the complete autonomy between the substantive law and process, showing this alienation has not been surpassed. Then, we analyze how the paradigm of modernity as the age of technique is projected in this relation, transforming the substantive law in the product of the process, in which the essence of the substantive law, what it really is, is not considered. We seek for elements which lead to the possibility of annihilation of the substantive law by the process, in which the substantive law is not what it is, but what the process tells it is. It is possible because the strength of the substantive law ? the action of substantive law has been denied. In this context, I aim at demonstrating the denial of the action of the substantive law subtracts the possibilities/presuppositions for the substantive law to take place in the process. The final desideratum is to fundament the hermeneutics task of the substantive law action. The theoretical basis is, concerning the substantive law action, in the doctrine of Pontes Miranda and Ovídio Araújo Baptista da Silva. The hermeneutics reading which is intended seeks, fundamentally, in Martin Heidegger and Hans-Georg Gadamer, the conditions of the possibility for unveiling the ideology which is the basis for the denial of the substantive law and the projection of an authentic view of the relation between the substantive law and process, in which the action of the substantive law is the source of irradiation of effects and tells to the process, like the mode of being of the substantive law. Finally, the effects of this new mode of viewing this relation and making law over some most discussed procedural institutes of the civil procedure is projected.
Keywords: Direito material; Processo; Ação de direito material; Pré-compreensão; Ideologia; Técnica; Exceção; Fenomenologia hermenêutica; Hermenêutica filosófica; Compreensão; Autenticidade; Concretização de pretensões; Substantive law; Process; Substantive law action; Pre-comprehension; Ideology; Technique; Exception; Hermeneutics phenomenology; Philosophical hermeneutics; Comprehension; Authenticity; Concretization of claims; ACCNPQ::Ciências Sociais Aplicadas::Direito